More than meets the eye: intra-operative retrograde pyelography when more than one ureteral obstruction is suspected - A case report - Marwa El Masri; Mehdi Mantash; Christina Abou-Malhab; Georges Aftimos; Pauline Abou-Jaoudeh; Nabil Diab (Elsevier, 2023)
Background: Antenatal hydronephrosis can be caused by various congenital anomalies of the excretory urinary system. Common causes are isolated ureteropelvic junction obstruction and ureterovesical junction obstruction with isolated mid-ureteral stenosis occurring much less frequently. To our knowledge, the co-existence of a triple ureteral obstruction has never been previously reported in the literature. Case presentation: We herein report the case of a 7-month-old girl who presented for follow up on antenatal hydronephrosis and was diagnosed with ureterovesical junction obstruction. After ureteroneocystostomy was done, failure to introduce the ureteral catheter into the ureter and subsequent dissection showed a second obstruction: a mid-ureteral valve, that was resected. Then, failure to re-introduce the catheter a second time with subsequent retrograde pyelography revealed a third obstruction: a ureteropelvic junction obstruction. Conclusion: The co-existence of multiple ureteral obstruction is a rare condition that poses diagnostic problems, and whose treatment remains challenging. Early diagnosis and treatment of these serious conditions is imperative because of their detrimental consequences on renal function. Thus, the occurrence of multiple ureteral obstruction should always be borne in mind and investigated intra-operatively by retrograde pyelography whenever suspected.